2017
DOI: 10.20944/preprints201701.0098.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Induction of G2M Arrest by Flavokawain A, A Kava Chalcone, Increases the Responsiveness of HER2 Overexpressing Breast Cancer Cells to Herceptin

Abstract: HER2/neu positive breast tumors predict a high mortality and comprise 25-30% of breast cancer. We have shown that Flavokawain A (FKA) preferentially reduces the viabilities of HER2 overexpressing breast cancer cell lines (i.e. SKBR3 and MCF7/HER2) versus those with less HER2 expression (i.e. MCF7 and MDA-MB-468). FKA at cytotoxic concentrations to breast cancer cell lines also has minimal effect on the growth of non-malignant breast epithelial MCF10 cells. FKA induces G2M arrest in cell cycle progression of HE… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The antiproliferative activity of chalcones is closely linked to cell cycle blockade and subsequent induction of apoptosis [ 171 ]. Tumor cell transformation, which may be the keystone for the development of cancer, may cause cells to be unresponsive to regulatory mechanisms and begin to divide uncontrollably.…”
Section: Cell Cycle and Tubulins As A Target Of Chalconesmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiproliferative activity of chalcones is closely linked to cell cycle blockade and subsequent induction of apoptosis [ 171 ]. Tumor cell transformation, which may be the keystone for the development of cancer, may cause cells to be unresponsive to regulatory mechanisms and begin to divide uncontrollably.…”
Section: Cell Cycle and Tubulins As A Target Of Chalconesmentioning
confidence: 99%
“…In addition, several other natural chalcones have been shown to cause G2/M arrest via suppression of cyclin levels or inhibition of CdKs activity including ISL [ 175 ], flavokawain A [ 171 ], XNT [ 57 ], FKB [ 176 ], CAR [ 177 ], butein [ 150 ], and many others.…”
Section: Cell Cycle and Tubulins As A Target Of Chalconesmentioning
confidence: 99%
“…G2/M cell cycle arrest is one of the key mechanisms employed by many cytotoxic drugs to inhibit the growth of cancer cells (Shapiro and Harper 1999). Recent literature suggested that cytotoxic drugs including Xerophilusin B and Flavokwain induce G2/M phase arrest in cancer cell lines (Yao et al 2015;Jandial et al 2017). To bring apoptotic death in the cancer cell a proper transmission of signals is essential but in cancer cells, the signalling mechanism is impaired and death is halted (Evan et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Flavokawain A (FKA), which is a novel chalcone from kava plant, can induce G2/M arrest and inhibit invasion and metastasis in several types of cancer [8][9][10]. In our previous study, we utilized the national medical products administration (NMPA) approved sodium aescinate (Aes) to stabilize hydrophobic PTX and FKA to form polymer-free PTX-A nanoparticles (NPs) and FKA-A NPs.…”
mentioning
confidence: 99%